Distribuição de probabilidades do eletrocardiograma na detecção de sobrecarga atrioventricular e marcadores eletrocardiográficos de distúrbios de despolarização e repolarização em cães com doença valvar crônica de mitral - Oliveira, Franciely Mota de (2019)
The electrocardiogram (ECG) is a rapid and available exam that can be used as a screening tool for detection of cardiac chamber enlargements, besides being a prognostic marker of several cardiac conditions. Through the analysis of several parameters, the ECG is able to identify changes that can be predictive of atrial and ventricular enlargement, besides detecting disturbances in the repolarization and depolarization process, playing an important role in the diagnosis of arrhythmias. The aim of this study was to evaluate the diagnostic capacity of the ECG in detecting left atrial and ventricular enlargement diagnosed on the echocardiogram. The ECG (ten leads) and echocardiogram examinations were carried out in 81 adult dogs, without distinction of race, sex or weight. The parameters indicative of atrial enlargement were P wave duration, PR interval, P area and Macruz index, in lead II; and P axis in leads I and III. As parameters of left ventricular enlargement, it was determined the Q, R and S wave amplitude and ST segment in lead II; Cornell's criterion in aVL and CV6LL; QRS axis in leads I and III; T wave amplitude and polarity in CV5RL; amplitude of the R and S wave in CV6LL and CV6LU. In echocardiogram were determined the left atrial/aortic ratio (LA/Ao), left interventricular septum (IVS), left ventricular internal diameter (LVID), left ventricular free wall thickness (LVFW), both in diastole. The results demonstrated that extrapolated human medicine parameters such as the P wave area and the Macruz index may be useful in the diagnosis of left atrial enlargement, however, it is necessary to establish normal values for the species in order to determine the probability distributions. Nevertheless, no evaluated electrocardiographic parameter shows good specificity and sensitivity in the detection of left atrial and ventricular enlargement. The present study also aimed to evaluate the electrocardiographic markers of depolarization and repolarization disorders in dogs with degenerative mitral valve disease (DMVD). Electrocardiographic evaluation was performed in 72 adult dogs, without distinction of breed, weight and sex, and they were divided into two groups. Group 1 was composed of 36 dogs diagnosed with DMVD and Group 2 of was composed of 36 control dogs without presenting the disease. Bipolar, unipolar and precordial leads were performed on the electrocardiogram (ECG). Atrial depolarization (P dispersion - Pd) and ventricular (QRS duration, QRS dispersion - QRSd) markers were measured, as well as markers of ventricular repolarization (QT interval, QT corrected - QTc and QT dispersion - QTd, Tpeak-Tend, Tpeak-Tend/QTc, Tpeak-Tend/JTpeak, JTpeak/JT). The mean values of Pd, QTd and QRSd were significantly higher in dogs with DMVD. These parameters also showed a significant positive correlation with the LA/Ao ratio. Dogs with DMVD have myocardial depolarization and repolarization disorders that may increase the likelihood of developing arrhythmias in these animals.